METODE BIMBINGAN KELUARGA DALAM MENGEMBANGKAN PENGETAHUAN AGAMA ISLAM ANAK - Amirullah, Bagus; Nuriya, Sinta (Universitas Al-Amien Prenduan, 2023)
The family guidance method is a well-organized way carried out by families or parents in carrying the burden of responsibility for the future of children by giving advice, setting an example, habituating, and supervising. Where the family is the main and first educator for their children. Therefore, families must be able to be role models for their children. The family is the first environment that is known to children before the child knows the outside environment. So families must pay attention, through appropriate family guidance methods so that they can instill Islamic religious values in children. For this reason, the focus and purpose of this research is to find out the methods and implementation of family guidance in developing children's Islamic religious knowledge in the family environment of the Al-Amien Prenduan Bani Djauhari Islamic Boarding School. The research method used in this research is descriptive qualitative method, because wanting to describe and describe what it is about the family guidance method in developing children's Islamic religious knowledge, the informants in this research are from Bani Djauhari. Data collection techniques are observation, interviews and documentation. Data analysis is data reduction, data display, data verification. The technique of checking the validity of the findings through hard training and triangulation. The results of the research are that the first method of family guidance that is applied in developing children's religious knowledge is the advice method, the story method, the dialogue method, the exemplary method, so that children can know or understand more about religion. The family provides support, provides all the learning tools needed. So that with the family guidance method, children can get to know their knowledge about religion better.Â